Effect of practice on performance of a skilled motor task in patients with Parkinson's disease. Issue 6 (June 1992) - Soliveri, P; Brown, R G; Jahanshahi, M; Marsden, C D
Abstract : Parkinson's disease leads to a breakdown in the execution of highly practised, skilled movements such as walking and handwriting. The improved execution of skilled movements with practice can be understood as a process of schema learning, the determining of the relevant parameters of the specific movement. The ability of patients with Parkinson's disease and age matched normal control subjects to improve their performance, with practice, on a skilled motor task, doing up buttons, was assessed. The task was assessed on its own and with simultaneous foot tapping. Both groups showed an initial improvement in the task on its own and deterioration in performance when buttoning with foot tapping. The amount of interference, however, decreased with practice, particularly in the patients with a 2 Hz tapping rate. The results suggest that patients with Parkinson's disease are capable of schema learning but require more practice than control subjects to achieve comparable levels of performance. This may be a reflection of the fundamental motor dysfunction of the disease rather than a specific learning deficit.